2017
DOI: 10.18632/oncotarget.15923
|View full text |Cite
|
Sign up to set email alerts
|

The relative efficacy and safety of targeted agents used in combination with chemotherapy in treating patients with untreated advanced gastric cancer: a network meta-analysis

Abstract: Gastric cancer is one of the leading mortal causes. Targeted therapy is a new type of cancer treatment, which precisely identifies and attacks cancer cells and significantly reduces side effects. In this network meta-analysis, we focused on the efficacy and safety of 12 targeted agents on gastric cancer among a total of 8,405 patients from 24 trials. Hazard ratio (HR) with 95% credible interval (CrI) were calculated for primary outcomes, including overall survival (OS) and progression-free survival (PFS), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…A previous network meta-analysis did not include apatinib, rilotumumab, regorafenib, etc. [10]. This study showed Ramucirumab to increase PFS, and endostar had superior results in 2-3 year PFS results.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A previous network meta-analysis did not include apatinib, rilotumumab, regorafenib, etc. [10]. This study showed Ramucirumab to increase PFS, and endostar had superior results in 2-3 year PFS results.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, targeted therapy was shown to be effective and safe for AGC. For agent selection, a recent network meta-analysis showed that ramucirumab and trastuzumab have significant advantages for improving OS and ramucirumab and endostar have significant advantages for improving PFS in AGC patients [10]. However, this study included randomized controlled trials (RCTs) which lack a blinded design so they could not eliminate psychological effects.…”
mentioning
confidence: 99%
“…Gastric cancer (GC) is considered the third-leading cause of death among all cancer types and has caused 723,000 deaths across the whole world. 1 , 2 Currently, the incidence of GC has been significantly increasing, with ~952,000 new cases each year. 2 The People’s Republic of China is a high-risk area for GC, and the new cases of GC in this region account for ~42.5% of such cases in the world.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Currently, the incidence of GC has been significantly increasing, with ~952,000 new cases each year. 2 The People’s Republic of China is a high-risk area for GC, and the new cases of GC in this region account for ~42.5% of such cases in the world. 3 Early GC can easily be misdiagnosed because of the small number of symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation